Teaching Araling Panlipunan: A Study of Challenges and Coping Mecha-nisms among Non-Social Studies Major Educators - David, Rowena May T. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
This research focused on the challenges and coping mechanisms of Non-Social Studies major teachers assigned to teach Araling Panlipunan in Bulacan, Philippines. This, therefore, makes the pressing call for comprehensive content knowledge, effective assessment strategies, collaborative approaches to teaching, and continuous professional development in order to fill the gap in expertise in teaching Philippine history, culture, and society. Key findings revealed that teachers belonging to the Non-Social Studies major often experience problems in their teaching brought about by insufficient subject-specific knowledge, which consequently affects their confidence and accuracy in content delivery. In this regard, it is proposed in the study a program on "Capacitating the Competence of the Non-Social Studies Major Teachers." This program seeks to enhance teaching competencies with focused interventions that equip teachers with necessary competencies and knowledge. These recommendations include a vertical professional learning community, teaching aids bank, and focused seminars and training programs. The study reinforces continuous learning and institutional support as ways to educational excellence and calls for future research into th impact of advanced degrees on teaching effectiveness.